STUDI ARAH KIBLAT PEMAKAMAN MUSLIM : ANTARA PRAKTEK DAN TEORI - hasan, Muhammad; Hidayatullah, Nur Fallah (ELFALAKY: Jurnal Ilmu Falak, 2022)
This research is motivated by the views of the people who think that the Qibla direction for the cemetery only faces west and uses estimates only. In generally, the purpose of this study was to determine the Qibla direction of Muslim graves. As for specifically knowing: 1) Measurement of the Qibla direction of Muslim graves. 2) The accuracy of the measurement results of the Qibla direction of Muslim graves. This research is limited to the Muslim cemetery in Dusun Pendamar Teluk Pakedai. The method used is a qualitative, with a descriptive approach. The primary data sources were the Village Head, Imam of the Ilaluddin Mosque, and the Tomb Manager in Pendamar Hamlet, Sungai Deras Village. Secondary data sources are obtained from documents, journals, and others. Data collection techniques used are observation, interviews, and documentation. The data collection tools used were rashdul kiblah, cameras, recording devices, and interview guidelines. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The last step is checking the validity of the data by using data triangulation and member check. This study concludes that: 1) To measure the Qibla direction of Muslim graves in Pendamar Hamlet, the community has carried out an estimation method, following the direction of the mosque's Qibla, and following the tombs that have been there before, and using a compass by facing right to the west. 2) All Muslim cemeteries that have been measured by the people of Dusun Pendamar use the approximate method, and follow the old grave, which is 2760 58' 29.27”, shows a very large deviation from the actual Qibla Azimuth which is 2920 48' 50.5”. So the researchers concluded that the Qibla direction was inaccurate with the difference in the Qibla direction being 150 50' 21.23”.